2016
DOI: 10.14257/ijast.2016.93.05
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Wear Behavior of High Velocity Oxy-Fuel Sprayed WC-CO Coatings

Abstract: The This paper examines the effect of WC-Co coatings on the wear behaviour, WC were thermally sprayed by a high-velocity oxy-fuel (HVOF) system from WC-12% Co powder. Sliding wear resistance of this coating was calculated using pin-ondisk tribometer (ASTM G99-90). The morphologies of WC-Co coating were observed by X-ray diffraction (XRD), Energy dispersive analysis and Scanning electron microscope (SEM). Micro hardness is calculated by using Vickers Hardness test. And it was found that WC-Co coatings show bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Wear tests were conceded out using a pin-on-disc tribometer (Figure 3), in accordance with the standards established by ASTM G99-95 [20]. The wear pins that are prepared have dimensions of 0.8 centimetres in width and 5 centimetres in height.…”
Section: Dry-sliding Wear Testmentioning
confidence: 99%
“…Wear tests were conceded out using a pin-on-disc tribometer (Figure 3), in accordance with the standards established by ASTM G99-95 [20]. The wear pins that are prepared have dimensions of 0.8 centimetres in width and 5 centimetres in height.…”
Section: Dry-sliding Wear Testmentioning
confidence: 99%
“…The properties of the metal-cutting tool are also modified [14], which increases its functional properties. High-speed deposition of WC-Co coatings, which ensures their high wear resistance, was investigated in [15]. Wear of hard coatings under dry friction containing tungsten, chromium and cobalt is considered in [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the interference structure of the coating depended on the morphology of substrate surface [15]. Mild steel pins coated with WC-12%Co displayed three times higher wear resistance than uncoated mild steel pins [16]. WC particles of range 5 % to 30 % was mixed with Cu particle and the mixture was made as coating on copper surface by solid-state sintering.…”
Section: Introductionmentioning
confidence: 99%